Pengaruh Literasi Keuangan pada Keuangan Inklusif Penggunaan Bank Sampah di Jakarta Selatan - Anna Sardiana (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2018)
Inclusive Finance is a national development strategy to encourage economic growth through equal distribution of income, poverty alleviation and financial system stability. Financial literacy measures inclusive finance through access to financial services that will greatly help marginalized and low-income groups to increase their revenues, accumulate wealth, manage risks, and make efforts to get out of poverty. This study aims to examine the effect of financial literacy with the variable of knowledge, ability and attitude / behavior on the inclusive financial use of garbage bank in South Jakarta. Method used in this research is descriptive method of analysis with quantitative approach, by using primary data. The analytical method used is multiple regression analysis with the help of SPSS 15.0 analysis tool